The Practice Environment Scale of the Nursing Work Index: An updated review and recommendations for use. (September 2017) - Swiger, Pauline A.; Patrician, Patricia A.; Miltner, Rebecca S. (Susie); Raju, Dheeraj; Breckenridge-Sproat, Sara; Loan, Lori A.
Abstract: Objectives: The Practice Environment Scale of the Nursing Work Index (PES-NWI) is an instrument, which measures the nursing practice environment – defined as factors that enhance or attenuate a nurse's ability to practice nursing skillfully and deliver high quality care. The purpose of this paper is to provide an updated review of the Practice Environment Scale of the Nursing Work Index's use to date and provide recommendations that may be helpful to nursing leaders and researchers who plan to use this instrument. Design: A narrative review of quantitative studies. Data sources: PubMed, EMBASE, and the Cumulative Index to Nursing & Allied Health Literature were searched to identify relevant literature using the search terms, Practice Environment Scale of the Nursing Work Index and PES-NWI . Review methods: Studies were included if they were published in English between 2010 and 2016 and focused on the relationship between the Practice Environment Scale of the Nursing Work Index and patient, nurse, or organizational outcomes. Data extraction focused on the reported survey scores and the significance and strength of the reported associations. Results: Forty-six articles, from 28 countries, were included in this review. The majority reported significant findings between the nursing practice environment and outcomes. Although some modifications have been made, the instrument has remained primarily unchanged since its development. Most often, the scores regarding staffing and resource adequacy remained the lowest. Conclusion: The frequency of use of this instrument has remained high. Many researchers advocate for a move beyond the study of the connection between the Practice Environment Scale and nurse, patient, and organizational outcomes. Research should shift toward identifying interventions that improve the environment in which nurses practice and determining if changing the environment results in improved care quality.